Pengaruh Latihan Range Of Motion (ROM) Ekstremitas Bawah Terhadap Perbaikan Ulkus Kaki Diabetik Pada Pasien Diabetes Melitus Tipe 2 di Ruang Rawat Inap Bedah Dewasa RSUD Kabupaten Ciamis - Devi Ratnasari (STIKes Karsa Husada Garut, 2014)
One of the chronic complications of type 2 diabetes mellitus is hyperglycemia that is tend tocontinue to the occurrence of diabetic ulcers as a result of perfusion disturbances andperipheral neuropathy. ROM (Range of Motion) exercise is one attempt to improve peripheral perfusion with the aim of facilitating the diffusion of oxygenated and inadequate supply of nutrients to the area of the ulcer as measured by the ankle brachial index / ABI and to the wound tissue repair process as measured withLeg Ulcer Measurement Tool / LUMT. The purpose of this study was to observe the effect of the lower extremity ROM exercises to the improvement of diabetic foot ulcers The design of this study using quasi-experimental pre-post test without a control group. Its population is patients with diabetic foot ulcers were treated in adult surgical inpatient unit Ciamis District Hospital. The results of consecutive sampling from June 3 to July 19, 2014were 22 people, but only 17 people who met the inclusion criteria. The lower extremity ROM exercises performed 3 times daily for 12 days and performed assessment on day 1 and day12. During the research wound care given are with the humid garamicyn care, diabetes diet,sub-cutaneous insulin therapy, and antibiotic therapy according to the results of bacterial culture. The results of the study there are influence between the lower extremity ROM to the improvement of diabetic foot ulcers (p = 0.000; r = 0.562) and the value of ABI (p = 0.000; r= 0.837). The lower extremity ROM exercises can be improvement peripheral perfusion with the aim of facilitating the diffusion of oxygenated and inadequate supply of nutrients to the area of the ulcer to the wound tissue repair process. Factors associated with peripheral perfusion is a history of smoking, andduration of diabetes mellitus, whereas factors related to the improvement of theulcer is the age, and hemoglobin levels. Conclusions of research there is influence between the lower extremity ROM exercises to theimprovement of diabetic foot ulcers in patients with type 2 diabetes mellitus in adult surgicalinpatient unit Ciamis District Hospital. This study can be used as a baseline for further studieswith different designs (quasi-experimental pre-post with control group).